The ALMA REBELS survey: the dust content of z ∼ 7 Lyman break galaxies. Issue 1 (3rd March 2022) - Dayal, P; Ferrara, A; Sommovigo, L; Bouwens, R; Oesch, P A; Smit, R; Gonzalez, V; Schouws, S; Stefanon, M; Kobayashi, C; Bremer, J; Algera, H S B; et al.
ABSTRACT: We include a fully coupled treatment of metal and dust enrichment into the Delphi semi-analytic model of galaxy formation to explain the dust content of 13 Lyman break galaxies (LBGs) detected by the Atacama Large millimetre Array (ALMA) REBELS Large Program at z ≃ 7. We find that the galaxy dust mass, M d, is regulated by the combination of Type II supernova dust production, astration, shock destruction, and ejection in outflows; grain growth (with a standard time-scale τ 0 = 30 Myr) plays a negligible role. The model predicts a dust-to-stellar mass ratio of 0.07\!-\!0.1 per cent and a UV-to-total star formation rate relation such that log(ψUV ) = −0.05 [log(ψ)] 2 + 0.86 log(ψ) − 0.05 (implying that 55–80 per cent of the star formation is obscured) for REBELS galaxies with stellar mass M_* = 10^9\!-\!10^10 M_ . This relation reconciles the intrinsic UV luminosity of LBGs with their observed luminosity function at z = 7. However, 2 out of the 13 systems show dust-to-stellar mass ratios (0.94\!-\!1.1 per cent ) that are up to 18 times larger than expected from the fiducial relation. Due to the physical coupling between dust and metal enrichment, even decreasing τ 0 to very low values (0.3 Myr) only increases the dust-to-stellar mass ratio by a factor of ∼2. Given that grain growth is not a viable explanation for such high observed ratios of the dust-to-stellar mass, we propose alternative solutions.